Respostas

2013-10-07T15:17:38-03:00
Através de sistema

x + y = 3
5x + 6y = 510
y = 3 - x

5x + 6(3 - x) = 510
5x - 6x + 18 = 510
-x = 510 - 18
x = -492

y = 3 + 492
y = 495

Reposta:
x = -492 e y = 495

  • Usuário do Brainly
2013-10-08T03:31:53-03:00
X + y = 3------y = 3 - x
5x + 6y = 510
---------------
substitui em 5x + 6y = 510
5x + 6.(3 - x) = 510
5x + 18 - 6x = 510
- x = 510 - 18
- x = 492 .(-1)
x = - 492
---------------
substitui em y = 3 - x
y = 3 - ( - 492)
y = 3 + 492
y = 495

S = { x , y }
S = { - 492, 495 }

Espero ter ajudado!